Digital Learning Orientation and Innovative Behavior : Learning Culture's Role in Sustainable Development Readiness - Farliana, Nina; Hardianto, Hanif; Rusdarti, Rusdarti; Sakitri, Wijang (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This research examines the influence of digital learning orientation on innovative work behavior, with readiness for change as a mediating factor and organizational learning culture as a moderating factor, as well as its contribution to sustainable development in Indonesia's education sector. This research utilizes the job demand-resource model and the social exchange theory framework. With a quantitative approach and clause associative design, the study population includes all active students from various disciplines at state universities in Central Java Province. The sample was selected using a non-probability sampling method of 218 respondents. Data collection was conducted through a questionnaire utilizing an interval scale ranging from strongly agree (scale 7) to strongly disagree (scale 1). The data were analyzed using the Structural Equation Modeling Partial Least Square (SEM-PLS) approach through the WarpPLS 5.0 software. The findings indicate that digital learning orientation indirectly influences innovative work behavior through readiness for change. Moreover, this indirect effect, mediated by readiness for change, is moderated by organizational learning culture, mainly when the moderation level is low. At an optimal level of organizational learning culture, digital learning orientation significantly boosts innovative behavior by promoting greater readiness for change. However, at this level, organizational learning culture no longer plays a significant role in predicting outcomes. The novelty of this study lies in incorporating organizational learning culture as a moderating factor in the connection between digital learning orientation and readiness for change in the context of sustainable development within the education sector.